2022
DOI: 10.3389/fendo.2022.869519
|View full text |Cite
|
Sign up to set email alerts
|

Secreted Protein Acidic and Rich in Cysteine Mediates the Development and Progression of Diabetic Retinopathy

Abstract: BackgroundsDiabetic retinopathy (DR) is one of the most severe microvascular complications of diabetes mellitus (DM). Secreted protein acidic and rich in cysteine (SPARC) has been found to play an important role in many diseases, but its role and mechanism in DR remain unknown.MethodsWe studied the role of SPARC and integrin β1 in vascular pathophysiology and identified potential therapeutic translation. The SPARC levels were tested in human serum and vitreous by ELISA assay, and then the Gene Expression Omnib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…81,82 This molecule is involved in the pathogenesis of several inflammatory diseases, including ulcerative colitis, diabetic retinopathy, and hemarthrosis. [83][84][85] To the best of our knowledge, in the obstetric field, only one study by McParland et al evaluated the effect of SPARC expression on the cleavage and rupture of fetal membranes at term and showed that the expression pattern of SPARC was primarily restricted to the fetal membranes overlying the cervix in the lower uterine segment prior to and during labor and within the rupture tear after delivery. 86 However, no study has focused specifically on the association between SPARC, IAI/MIAC, and SPTB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…81,82 This molecule is involved in the pathogenesis of several inflammatory diseases, including ulcerative colitis, diabetic retinopathy, and hemarthrosis. [83][84][85] To the best of our knowledge, in the obstetric field, only one study by McParland et al evaluated the effect of SPARC expression on the cleavage and rupture of fetal membranes at term and showed that the expression pattern of SPARC was primarily restricted to the fetal membranes overlying the cervix in the lower uterine segment prior to and during labor and within the rupture tear after delivery. 86 However, no study has focused specifically on the association between SPARC, IAI/MIAC, and SPTB.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, SPARC exerts anti‐inflammatory responses via a negative regulation of nuclear factor‐kB and tumor necrosis factor (TNF)‐β signaling 81,82 . This molecule is involved in the pathogenesis of several inflammatory diseases, including ulcerative colitis, diabetic retinopathy, and hemarthrosis 83–85 . To the best of our knowledge, in the obstetric field, only one study by McParland et al.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that leptin induces SPARC expression in adipose tissue and that SPARC expression was then correlated with IL-6 and fasting insulin levels [150]. SPARC has also been shown to further retinopathy in individuals with diabetes by interacting with VEGF and PAI-1 in endothelial cells [151]. In a 3D in vitro vasculature model, leptin was also shown to have profibrotic effects, indicated by the upregulation of collagens II and IV and the downregulation of MMPs 2 and 9 [28,80].…”
Section: Extracellular Matrix Remodeling During Obesitymentioning
confidence: 99%
“…Overexpression of SPARC is capable of disrupting the integrity of vascular endothelial cell layers, affecting matrix composition and cell adhesion, thus facilitating the invasion and metastasis of tumors (106,108,109). SPARC knockdown reduces the expression levels of inflammatory factors and VEGFR, downregulating ECs apoptosis, and angiogenesis in diabetic retinopathy (110). SPARC is a key factor in angiogenesis and endothelial barrier function which is well established; however, the underlying mechanism of RA-induced angiogenesis has not yet been defined.…”
Section: Sparcmentioning
confidence: 99%